2004
DOI: 10.2355/isijinternational.44.123
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Hammering Hydroforming by Static Explicit FEM

Abstract: Recently, tube hydroforming is receiving increasing attention. Knowledge on the process is, however, still insufficient to produce high-quality products in an efficient way. Hammering hydroforming, in which the hydraulic pressure is pulsated synchronously with axial feeding, is an effective method of improving forming ability. However, the factors that cause the improvement are still unclear. In the research reported in this paper, simulations of an automotive component produced by hammering hydroforming have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 14 publications
0
16
0
Order By: Relevance
“…Hama et al [7] have claimed that the same effect achieved by lowering the friction coefficient could be obtained by pulsing the pressure. However, since the frequency of the ultrasonic vibration is much higher than that used in pulsating hydroforming, a different mechanism to achieve this aim is still required [11].…”
Section: Introductionmentioning
confidence: 92%
“…Hama et al [7] have claimed that the same effect achieved by lowering the friction coefficient could be obtained by pulsing the pressure. However, since the frequency of the ultrasonic vibration is much higher than that used in pulsating hydroforming, a different mechanism to achieve this aim is still required [11].…”
Section: Introductionmentioning
confidence: 92%
“…The effect of loading path on the formability has been investigated by many researchers [3][4][5] and the guideline on designing the loading path is gradually acquired. Recently, the loading paths in which the hydraulic pressure is raised to a certain magnitude in advance of the axial pushing and then the hydraulic pressure and the axial pushing are simultaneously given, are considered to be effective to obtain the good formability, and are employed to product many practical components [2,6]. This type of loading path is generally called the pressure advanced type and this knowledge is also found in the experiments conducted by Yoshida et al [4].…”
Section: Introductionmentioning
confidence: 97%
“…4 Mori and colleagues [5][6][7] examined the mechanism of improvement of formability by experiments and simulations of tube hydroforming under monotonic increasing internal pressure and pulsating internal pressure. It was found that the occurrences of bursting and buckling were prevented by the oscillation of pressure, and the wall thickness of the formed tube was also improved by the oscillation.…”
Section: Introductionmentioning
confidence: 99%